Levels of brominated flame retardants in blood in relation to levels in household air and dust - Karlsson, M.; Julander, A.; van Bavel, B.; Hardell, L. (Environment international, 2007)
Levels of tri- to decabrominated diphenyl ethers (BDEs), 1,2- bis(2,4,6-tribromophenoxy)ethane (BTBPE) and 1,2- bis(pentabromophenyl)ethane (DeBDethane) were determined in air, sedimentary dust and human plasma from five households in Sweden. The levels of the individual BDEs in the plasma samples were in the same order of magnitude as in other studies of the general population in Scandinavia, and varied between non-detectable (< 0.41 ng g − 1 l.w.) to 17 ng g − 1 (l.w.). BDE#28 and #47 were present in all air samples, with mean values of 0.015 and 0.12 ng m − 3 , respectively, except for one sample where the BDE#47 concentration was below the limit of detection (< 0.17 ng m − 3 ). BDE#209 was found in one of the five air samples at a concentration of 0.26 ng m − 3 . DeBDethane was also detected in one sample, in which the BDE#209 level was below LOD (< 0.021 ng m − 3 ), at a level of 0.023 ng m − 3 . All the target compounds were found in the sedimentary dust samples at levels from 0.51 to 1600 ng g − 1 , the highest concentration representing BDE#209. The most abundant components in plasma, air and dust were BDE#47, #99 and #209. In the plasma samples BDE#207 and #206 were also present at similar concentrations as BDE#47. In the sedimentary dust samples, DeBDethane was also among the most abundant BFRs. A positive relationship was found for the sumBDE concentrations in dust and plasma, although the relationship was strongly dependent on one of the five observations. BFR levels in dust and air were not dependent on the house characteristics such as living area, floor material or number of electronic devices.